CHRONIC WOUNDS: PREVENTION, TREATMENT AND REHABILITATION - Quitéria Fernandes Ferreira, Ana; Carolinne Marie dos Santos Gomes, Anne; Ellen Costa Vasconcelos, Eduarda; Carolina Salustino dos Santos, Maria (Health and Society, 2023)
Wounds, due to their complexity, end up impairing the functioning of the skin, causing disability or loss of function, in some cases, they can affect the patient’s general condition, especially when not properly treated, which can lead to severe infections or sepsis and lead the individual to the death. Symptoms such as low self-esteem, lack of motivation, social and work changes, deficits in quality of life and changes in self-image can also be attributed.